Improving Students’ Writing News Text Ability through a Process Approach with Audio Visual Media at The Eighth Grade of MTs Negeri 1 Lampung Timur - Mala, Elvita; Supriyono, Supriyono; Rohana, Rohana; Wahyuningsih, Sri (IJLHE: International Journal of Language, Humanities, and Education, 2019)
This study aims to improve the students’ writing news text ability through a process approach with audio-visual media at the eighth grade of MTs Negeri 1 Lampung Timur. This research method is Classroom Action Research (CAR). Data collection techniques in research are observation, documentation, and tests. Observational data analysis techniques and news text writing tests. Based on the analysis of observational data, the students’ writing news text ability through a process approach with audio-visual media at the eighth grade of MTs Negeri 1 Lampung Timur in the first cycle, which is 69.72 with an average value of 56.25% classical success indicators. In the second cycle that is equal to 71.87% with an average value of 87.5% classical success indicator. In the third cycle increased by 80.62% with an average value of 87.5% classical success indicator. Based on the results of the study, it was concluded that there was an improve the students’ writing news text ability through a process approach with audio-visual media at the eighth grade of MTs Negeri 1 Lampung Timur.